Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T17:49:21+01:00
(x-1)(x+1)-x²=2-x-y
(x-1)²+(y+1)²=x²+y²

x² - 1 - x²= 2 - x - y
x² - 2x + 1 + y² + 2y + 1 = x² + y²

-1 = 2 - x - y
-2x + 1 + 2y + 1 = 0

x + y = 3
2x - 2y = 2

x + y = 3
x - y = 1

x + y = 3
x = 1 + y

1 + y + y = 3
x = 1 + y

y = 1
x = 1 + 1 = 2


1 5 1
2009-12-02T17:53:52+01:00
(x-1)(x+1)-x²=2-x-y
(x-1)²+(y+1)²=x²+y² korzystam z wzorów skróconego mnożenia

x²-1-x²=2-x-y
x²-2x+1+y²+2y+1=x²+y²

x+y=3
-2x+2y=-2/:2

x+y=3
-x+y=-1 dodaję stronami
-----------
2y=2/:2
y=1
x=3-1
x=2

x=2
y=1
1 5 1